Economic Income as a Cause of Stunting: an Analysis Based on the Perspective of Karl Marx: Literature Review - Latif, Sarifudin Andi; Adam, Arlin; Kamaruddin, Syamsu A (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: Stunting begins to appear when the child is two years old and begins when the fetus is still in the womb. The increase in child morbidity and mortality is the impact caused by the incidence of stunting. Stunting children will be able to experience disturbances in their intelligence level, susceptibility to diseases, decreased productivity, and stunted economic growth, which impacts poverty. Method: This study is a literature review using the PRISMA method. Articles published in 2022-2024 were found by conducting database searches (Garuda and Google Scholar) and using the keywords "Stunting" and "Economic Income," and limited to using Chi-Square analysis so that articles meet the criteria for analysis, as many as 10 articles. Results: The search results for the ten articles were obtained, all stating the relationship between economic income and stunting. The author claims that Karl Marx's point of view highlights this problem as a social problem from a social system that subjugates a particular economic class. Dependence on the wage system, inadequate social security, and the exploitation of labor by capitalism trap many proletarian families in a cycle of poverty. This leaves children in these homes vulnerable to chronic malnutrition, which adversely affects their physical and cognitive development. Conclusion: The problem of low economic income in society as the cause of stunting is not only technical interventions, such as supplementary nutrition programs, but rather more fundamental structural changes, as seen from a Marxist perspective. Systematic reduction of economic inequality and stunting prevention can be achieved through wealth redistribution, wage system improvement, and labor exploitation elimination.